2020
DOI: 10.1016/j.critrevonc.2020.103043
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic reirradiation for local failure of brain metastases following previous radiosurgery: Systematic review and meta-analysis

Abstract: Introduction: Local failure (LF) following stereotactic radiosurgery (SRS) of brain metastases (BM) may be treated with a second course of SRS (SRS2), though this procedure may increase the risk of symptomatic radionecrosis (RN). Methods: A literature search was conducted according to PRISMA to identify studies reporting LF, overall survival (OS) and RN rates following SRS2. Meta-analysis was performed to identify predictors of RN. Results: Analysis included 11 studies (335 patients,389 metastases). Pooled 1-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…There is a balance between tumor coverage and normal tissue toxicity, and the dose prescribed for 2 nd SRS is variable [4,6,10,11,24]. At our institution, the dose prescribed for the tumor was essentially the same during retreatment.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…There is a balance between tumor coverage and normal tissue toxicity, and the dose prescribed for 2 nd SRS is variable [4,6,10,11,24]. At our institution, the dose prescribed for the tumor was essentially the same during retreatment.…”
Section: Discussionmentioning
confidence: 97%
“…While SRS has been considered an optimal treatment strategy for limited recurrent BM lesions [2,4], there is no consensus treatment recommendations [2] and the prescribed treatment dose for the 2 nd SRS is variable in published studies [4,6,10,11,24]. In this study, we modeled the TCP for 46 recurrent and 349 non-retreatment BM lesions to predict the relation between local control and dose delivered to the tumor volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a few predictive nomograms have also been developed in the context of oligometastatic NSCLC. One nomogram model found that KPS, primary tumor histology, primary tumor control, size of the largest metastasis, and the number of metastases (1 vs. >1) were significant prognostic factors for OS after SBRT [ 62 ]. A smaller, more recent study showed that the solitary site of metastasis, targetable mutations, intracranial disease, and metachronous oligometastases were all predictive of larger PFS benefits after LAT [ 63 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Recently, we described the development of the first software allowing the integration of metabolic cartography based on multivoxel spectroscopic MRI in the radiosurgical planning for Leksell Gamma Knife Radiosurgery. The few existing meta-analysis could not lead to gold standard volume delineation techniques despite objective advance in imaging assessment [8,9]. Prospective studies using multimodal imaging data will help to overcome this insufficiency for target delineation in radiosurgery.…”
mentioning
confidence: 99%